PENUNDAAN PEMOTONGAN TALI PUSAT TERHADAP APGAR SCORE BAYI BARU LAHIR - Mutiara Dwi Yanti; Mardiah Mardiah; Peny Ariani; Andayani Boang Manalu (Universitas Pahlawan Tuanku Tambusai, 2020)
Asphyxia is a condition in which the baby cannot immediately breathing spontaneously and regularly after birth. Fitness assessments in infants can be calculated using APGAR Score in the first minute and the fifth minute of the newborn.The purpose of research to determine the effect of clamping APGAR Score improvement newborns at Sembiring Hospital at Del Serdang. The research design used is Quasy Experiment using Pre Experimental Design using PostTest Only Design. The technique used for sample withdrawal is Purpossive Sampling. Analysts are expected to use bivariate analysis to determine the effect of cord cutting delays. Normality test data using sharpiro-wilk test, for bivariate analysis test conducted by tha Mann-whitney test, P-value result 0.000